Mobile Gamification and Purchase Intention: Evidence from Traveloka - Rizki Yudhi Dewantara; M. Alif Elijah Veron (Manajemen Multitalenta Indonesia, 2025)
The increasing competitiveness among online travel agencies (OTAs) has encouraged companies to innovate through user‐engagement strategies such as mobile gamification. Gamification refers to the integration of game elements into non‐game contexts to enhance users’ enjoyment, motivation, and behavioral intentions. This study investigates the effect of gaming affordances on purchase intention, mediated by enjoyment, among users of the Traveloka mobile application in Indonesia. Using an explanatory quantitative design, data were collected from 115 respondents who had previously interacted with Traveloka’s gamified features. The analysis employed path analysis using SPSS version 29. Results indicate that gaming affordances particularly achievement, identity, and competition affordances significantly influence enjoyment, while self‐expression affordance shows a positive but nonsignificant relationship. Furthermore, enjoyment significantly predicts purchase intention, confirming its mediating role between gaming affordances and user behavioral intention. These findings demonstrate that well‐designed gamification elements can enhance user experience and drive purchase decisions in mobile travel platforms. Implications for OTA developers and future research directions are also discussed.